Expanding repertoires of resistance: Teachers cultivating critical English language arts pedagogies through collaborative narrative inquiry. Issue 2 (3rd June 2019) - Taylor, Kara Michelle; Taylor, Evan M.; Hartman, Paul; Woodard, Rebecca; Vaughan, Andrea; Coppola, Rick; Rocha, Daniel J.; Machado, Emily
Abstract : Purpose: This paper aims to examine how a collaborative narrative inquiry focused on cultivating critical English Language Arts (ELA) pedagogies supported teacher agency, or "the capacity of actors to critically shape their own responsiveness to problematic situations" (Emirbayer and Mische, 1998, p. 971). Design/methodology/approach: Situated in a semester-long inquiry group, eight k-16 educators used narrative inquiry processes (Clandinin, 1992 ) to write and collectively analyze (Ezzy, 2002 ) stories describing personal experiences that brought them to critical ELA pedagogies. They engaged in three levels of analysis across the eight narratives, including open coding, thematic identification, and identification of how the narrative inquiry impacted their classroom practices. Findings: Across the narratives, the authors identify what aspects of the ELA reading, writing and languaging curriculum emerged as problematic; situate themselves in systems of oppression and privilege; and examine how processes of critical narrative inquiry contributed to their capacities to respond to these issues. Research limitations/implications: Collaborative narrative inquiry between teachers and teacher educators (Sjostrom and McCoyne, 2017 ) can be a powerful method to cultivate critical pedagogies. Practical implications: Teachers across grade levels, schools, disciplines and backgrounds can collectively organize to cultivate critical ELA pedagogies. Originality/value: Although coordinated opportunities to engage in critical inquiry work across k-16 contexts are rare, the authors believe that the knowledge, skills and confidence they gained through this professional inquiry sensitized them to oppressive curricular norms and expanded their repertoires of resistance.